Mechanisms of Cannabis Growth Promotion by Bacillus velezensis S141 - Phirom Aunkam; Surachat Sibponkrung; Sirawich Limkul; Tuangrak Seabkongseng; Kanjana Mahanil; Kamolchanok Umnajkitikorn; Nantakorn Boonkerd; Neung Teaumroong; Shusei Sato; Panlada Tittabutr; Pakpoom Boonchuen (Plants)
Cannabis sativa L. has a variety of uses, including fiber production, food, oil, and medicine. In response to environmental concerns regarding chemical fertilizers, Bacillus velezensis S141 was examined as a plant-growth-promoting bacterium (PGPB) for cannabis. This study evaluated the effects of S141 on cannabis growth and utilized transcriptomic analysis to identify the responsive pathways. Inoculation with S141 significantly increased growth in laboratory and field environments, with most of the bacteria residing in the leaves, followed by the stems and roots, as determined by quantitative polymerase chain reaction (qPCR). Transcriptomic analysis revealed 976 differentially expressed genes. Upregulated genes were associated with metabolism, cellular processes, and catalytic activities, especially in the biosynthesis of phenylpropanoid, plant–pathogen interactions, and hormone signaling pathways. S141 mutants deficient in the production of auxin and cytokinin displayed reduced growth enhancement, which affirmed the roles of these hormones in cannabis development. These findings emphasize the potential of S141 as a sustainable growth promoter for cannabis and provide insights into the underlying pathways it influences.